Design of a Microchannel‐Nanochannel‐Microchannel Array Based Nanoelectroporation System for Precise Gene Transfection. Issue 5 (31st October 2013) - Gao, Keliang; Li, Lei; He, Lingna; Hinkle, Kevin; Wu, Yun; Ma, Junyu; Chang, Lingqian; Zhao, Xi; Perez, Daniel Gallego; Eckardt, Sigrid; Mclaughlin, John; Liu, Boyu; et al.
<x xml:space="preserve">Abstract</x> A micro/nano‐fabrication process of a nanochannel electroporation (NEP) array and its application for precise delivery of plasmid for non‐viral gene transfection is described. A dip‐combing device is optimized to produce DNA nanowires across a microridge array patterned on the polydimethylsiloxane (PDMS) surface with a yield up to 95%. Molecular imprinting based on a low viscosity resin, 1, 4‐butanediol diacrylate (1, 4‐BDDA), adopted to convert the microridge‐nanowire‐microridge array into a microchannel‐nanochannel‐microchannel (MNM) array. Secondary machining by femtosecond laser ablation is applied to shorten one side of microchannels from 3000 to 50 μm to facilitate cell loading and unloading. The biochip is then sealed in a packaging case with reservoirs and microfluidic channels to enable cell and plasmid loading, and to protect the biochip from leakage and contamination. The package case can be opened for cell unloading after NEP to allow for the follow‐up cell culture and analysis. These NEP cases can be placed in a spinning disc and up to ten discs can be piled together for spinning. The resulting centrifugal force can simultaneously manipulate hundreds or thousands of cells into microchannels of NEP arrays within 3 minutes. To demonstrate its application, a 13 kbp OSKM plasmid of induced pluripotent stem cell (iPSC) is injected into mouse embryonic fibroblasts cells (MEFCs). Fluorescence detection of transfected cells within the NEP biochips shows that the delivered dosage is high and much more uniform compared with similar gene transfection carried out by the conventional bulk electroporation (BEP) method.